Medical Tourism in Davao City - Casurao, Gypsy Mae; Velila, Jeanova (La Ricerca, 2019)
The aim of this study was to determine the perception of the tourism stakeholders towards medical tourism as well as the factors influencing the development of medical tourism in Davao City. A qualitative research method was adopted to collect data from representatives of Department of Tourism Region XI, Davao Doctors Hospital, Ricardo Limso Medical Center, City Tourism members, Locals, Educators and Medical tourists. The results revealed the in terms of services respondents’ perceived that it is existing and effective. They attest its effectivity through patronizing cosmetic product and appreciating prices of the product. On the other hand, In terms of benefits, respondents believe that medical tourism benefits are indeed helpful. The respondents thought that these benefits are visible especially in the economic growth of the City. In terms of Challenges, the respondents perceived challenges as factor that needs to be considered for it affects medical tourism as a whole. A number of respondents emphasized the lack of promotion as the major challenge in pushing medical tourism in Davao City. In terms of future development, respondents’ perceived future development as something that should be implemented for the betterment of medical tourism in Davao City.